Lucid Dreaming: A State of Consciousness with Features of Both Waking and Non-Lucid Dreaming - Voss, Ursula (Associated Professional Sleep Societies, LLC, 2009)
STUDY OBJECTIVES: The goal of the study was to seek physiological correlates of lucid dreaming. Lucid dreaming is a dissociated state with aspects of waking and dreaming combined in a way so as to suggest a specific alteration in brain physiology for which we now present preliminary but intriguing evidence. We show that the unusual combination of hallucinatory dream activity and wake-like reflective awareness and agentive control experienced in lucid dreams is paralleled by significant changes in electrophysiology. DESIGN: 19-channel EEG was recorded on up to 5 nights for each participant. Lucid episodes occurred as a result of pre-sleep autosuggestion. SETTING: Sleep laboratory of the Neurological Clinic, Frankfurt University. PARTICIPANTS: Six student volunteers who had been trained to become lucid and to signal lucidity through a pattern of horizontal eye movements. MEASUREMENTS AND RESULTS: Results show lucid dreaming to have REM-like power in frequency bands δ and θ, and higher-than-REM activity in the γ band, the between-states-difference peaking around 40 Hz. Power in the 40 Hz band is strongest in the frontal and frontolateral region. Overall coherence levels are similar in waking and lucid dreaming and significantly higher than in REM sleep, throughout the entire frequency spectrum analyzed. Regarding specific frequency bands, waking is characterized by high coherence in α, and lucid dreaming by increased δ and θ band coherence. In lucid dreaming, coherence is largest in frontolateral and frontal areas. CONCLUSIONS: Our data show that lucid dreaming constitutes a hybrid state of consciousness with definable and measurable differences from waking and from REM sleep, particularly in frontal areas. CITATION: Voss U; Holzmann R; Tuin I; Hobson A. Lucid dreaming: a state of consciousness with features of both waking and non-lucid dreaming. SLEEP 2009;32(9):1191-1200.